2012
DOI: 10.1371/journal.pone.0046677
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin2 Promotes Invasion, Tumorigenicity and Gemcitabine Resistance in Pancreatic Ductal Adenocarcinoma

Abstract: Lipocalin 2 (LCN2) is a small secreted protein and its elevated expression has been observed in pancreatic as well as other cancer types. LCN2 has been reported to promote resistance to drug-induced apoptosis, enhance invasion through its physical association with matrix metalloproteinase-9, and promote in vivo tumor growth. LCN2 was found to be commonly expressed in patient PDAC samples and its pattern of immunohistochemical staining intensified with increasing severity in high-grade precursor lesions. Downre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 30 publications
1
71
0
1
Order By: Relevance
“…However, activity in these tissues is most probably related to one or more of the multifaceted functions of this molecule identified in other tissues. These include promoting angiogenesis [21] and enhancing matrix degradation through interactions with MMP9 [16]. With respect to the latter activity, dimerization of Lcn2 with proMMP9 appears to enhance activation of the enzyme by plasma kallikrein and protects the enzyme from degradation [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, activity in these tissues is most probably related to one or more of the multifaceted functions of this molecule identified in other tissues. These include promoting angiogenesis [21] and enhancing matrix degradation through interactions with MMP9 [16]. With respect to the latter activity, dimerization of Lcn2 with proMMP9 appears to enhance activation of the enzyme by plasma kallikrein and protects the enzyme from degradation [22].…”
Section: Discussionmentioning
confidence: 99%
“…Lenti-X 293T cells were transfected with the respective expression vectors coding for the tribody [(Her2) 2 (29). The tribody was purified from supernatant as described (29,30).…”
Section: Expression and Purification Of The Antibody Derivativesmentioning
confidence: 99%
“…Approximately 80% of the patients have an advanced disease with distant metastases at diagnosis, and only 10% to 20% are accessible for surgical resection (1). Occasional resistance of PDAC to chemotherapy demanded alternative therapeutic approaches (2,3). An increasing number of novel therapeutic strategies, including targeted therapy or immunotherapy alone or in combination with chemotherapy, have been described but still failed to considerably improve survival times of the patients (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…There has been some research on the resistance aspects of gemcitabine and 5-FU. Leung et al found that suppression of Lipocalin2 (LCN2) in PC cells increased their sensitivity to gemcitabine in vitro, and in vivo (43). Awasthi et al reported that insulin-like growth factor (IGF) signaling proteins are frequently overexpressed in pancreatic duct adenocarcinoma (PDAC), and using a small molecular inhibitor of IGF receptor (BMS-754807) was able to enhance gemcitabine response in PC (44).…”
Section: Discussionmentioning
confidence: 99%